Analisis Alur Penerimaan, Permintaan dan Pengeluaran Bahan Kimia di Gudang Kimia PT. XYZ - Pangestu, Bilal Setiyo; Enny Aryanny (Pusat Riset dan Inovasi Nasional, 2024)
PT XYZ is a company that produces newsprint and printed writing paper. In its production, the company needs raw materials to support the paper production so that it can be produced optimally. This research is used to find out how companies can optimize production by considering the flow of in and out of chemical raw materials used as materials to produce paper according to consumer wishes.